Strategi Pembelajaran Menulis Karangan Narasi Bagi Siswa Sekolah Dasar Menggunakan Kurikulum Merdeka Belajar: Learning Strategies for Writing Narrative Essay for Primary School Students Using Merdeka Belajar Curriculum - Astutik, Dwi Widi; Rahmawati, Dian Nur; Anggraini, Ade Eka; Dewi, Radeni Sukma Indra (Universitas Nusantara PGRI Kediri, 2024)
Learning Indonesian is mandatory learning given in elementary schools. There are four skills that students must master in learning Indonesian, namely listening, speaking, reading and writing skills. One of the language skills that is considered difficult for students is writing skills. This condition is motivated by students having difficulty expressing their creative ideas into writing. Implementing learning strategies can support the achievement of learning essay writing skills, in this case narrative essays. This research aims to identify through literature studies appropriate learning strategies in learning to write narratives for elementary school students. The method used is a descriptive qualitative research method. Data was collected through literature studies from various sources ranging from articles, books, theses and theses that examine learning to write narratives. The results of this research show that there are various strategies that can be implemented in learning to write narrative essays, starting from implementing approaches, models, methods, to utilizing learning media so as to create learning that suits needs and achieves material achievement indicators.